AGE-RELATED ASPECTS OF VEGETATIVE STATUS IN CHILDREN WITH VEGETATIVE DYSTONIA SYNDROME - V. A. Shashel; L. A. Podporina; G. B. Panesh; D. S. Ponomarenko; P. E. Dobryakov (Кубанский научный медицинский вестник, 2017)
Aim. Of the study is to assess the vegetative status of children with vegetative dystonia syndrome.Materials and methods. The vegetative status was studied in 811 children and adolescents under the age of 17 years with a syndrome of vegetative dystonia who applied for medical assistance in the consultative and diagnostic department of the Children's Regional Clinical Hospital of the Ministry of Healthcare of Krasnodar Krai during 2016. To study the functioning of the autonomic nervous system, the сardiointervalography (CIG) was used. When assessing the state of the autonomic nervous system, the initial vegetative tonus (IVT), vegetative reactivity (VR), stability of vegetative processes regulation and activity of subcortical nerve centers (ASNC) were taken into account.Results. In 37.6% of the patients examined, the predominance of the parasympathetic nervous system tone was noted, in 28.9% of children the sympathetic department dominated, in 33.5% of the cases the eutonium was recorded. Hypersympathicotonic autonomic reactivity was registered in 50% of children, asymptaticotonic – in 22.9% of cases, within the normal limits – 27.1%. Stable regulation of vegetative processes was observed in 42.3% of patients, dysregulation with prevalence of parasympathetic nervous system was identified in 21.8% of cases, dysregulation with prevalence of sympathetic nervous system – in 13.5% of patients, a central type of dysregulation was observed in 11.8% of patients and a transient process – in 10.6% of cases. An increase in subcortical nerve centers activity was detected in 47% of the children and adolescents examined, an activity decrease was registered in 25.9% of the examined, normal activity was detected in 27.1% of cases. The evaluation of autonomic reactivity in children with clinical manifestations of autonomic dystonia syndrome according to the CIG was characterized as follows: initially, vegetative reactivity was increased in 66.2% of girls aged 5 to 9 years, in 33.8% it was decreased. In the age range from 10 to 14 years, the schoolchildren are strongly dominated by the increase in vegetative reactivity – 85.0%, the indicator is decreased in 15.0% of patients. 15-17 years old girls with hypersympaticotonic reactivity prevail – 88.0% of patients, while there were only 12.0% of patients with registered asympathicotonic reactivity. 5-9 years old boys of with defined hypersympathicotonic reactivity make 73.7%, with asymptoticotonic reactivity – 26.3%. Age from 10 to 14 years is represented by the following results: 91.5% of boys are characterized by increased vegetative reactivity and only 8.5% by decreased vegetative reactivity. In young men aged 15- 17 years, the prevalence of hypersympathicotonic dystonia is expressed, the incidence of increased vegetative reactivity increases significantly.Conclusion. With the increase of years of children suffering from vegetative dystonia syndrome without considering gender factors, the parasympathetic orientation of the vegetative tonus increases. The regulation of vegetative processes in most children is stable when the activity of the subcortical nerve centers is increased.